2019
DOI: 10.1093/mmy/myz093
|View full text |Cite
|
Sign up to set email alerts
|

The detection of Coccidioides from ambient air in Phoenix, Arizona: Evidence of uneven distribution and seasonality

Abstract: Coccidioidomycosis is a debilitating fungal disease caused by inhalation of arthroconidia. We developed a novel approach for detection of airborne Coccidioides and used it to investigate the distribution of arthroconidia across the Phoenix, Arizona, metropolitan area. Air filters were collected daily from 21 stationary air-sampling units across the area: the first set collected before, during and after a large dust storm on August 25, 2015, and the second over the 45-day period September 25–November 8, 2016. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 23 publications
1
42
1
Order By: Relevance
“…For instance, the bacteria Vibrio cholerae found in domestic sewage can result in severe gastroenteritis, which causes dehydration and death (Moehling et al 2020). Opportunistic fungal pathogens such as Penicillium, Paracoccidioides and Coccidioides from urban effluents are involved in respiratory tract infections (Yu et al 2005;Gade et al 2020;Singulani et al 2020). The inputs of agricultural waste water with high phosphorus concentrations are responsible for the presence and abundance of both fungal and bacterial pathogens (Duarte et al 2015;Wu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the bacteria Vibrio cholerae found in domestic sewage can result in severe gastroenteritis, which causes dehydration and death (Moehling et al 2020). Opportunistic fungal pathogens such as Penicillium, Paracoccidioides and Coccidioides from urban effluents are involved in respiratory tract infections (Yu et al 2005;Gade et al 2020;Singulani et al 2020). The inputs of agricultural waste water with high phosphorus concentrations are responsible for the presence and abundance of both fungal and bacterial pathogens (Duarte et al 2015;Wu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Gade et al. ( 2020 ) suggest that this is initial evidence that large dust storms might even temporarily reduce airborne arthroconidia counts. Furthermore, on the dust storm day, the positive sites were not spatially clustered and they were intermingled between sites with no detected spores, enabling two deductions relevant to the present study: (a) the source of the arthroconidia must have been local (within a few kilometers based on site location spacing, possibly much less, assuming the dust in the storm was well‐mixed as seen in Figure 1 ) meaning the dust storm did not supply arthroconidia from its dust source region outside the city, and (b) neither did the dust storm spread arthroconidia widely across the urban area—concentrations remained highly localized.…”
Section: Introductionmentioning
confidence: 95%
“…A recent study in Phoenix, AZ provided especially valuable insights into the varying concentrations, seasonality and locally uneven spatial distribution of airborne Coccidioides spores (Gade et al., 2020 ). One set of samples characterized concentrations of arthroconidia on the days before, during and after a major dust storm on 25 August 2015 (the haboob illustrated in Figure 1 ); positive samples were found at 18 of 21 (86%) sites on the day before the dust storm, while only four sites (19%) were positive on the day of the dust storm and on the day after.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent study, air was sampled and filtered from 21 sites in the Phoenix metropolitan area on a specific day after a dust storm as well as over a 45-day period during the fall. DNA was extracted from the filters and subjected to nested qPCR [ 25 ]. Although prior evidence has suggested that dust storms are associated with outbreaks of coccidioidomycosis [ 26 ], there was actually a decrease in positive filter samples from sites on the days immediately after the dust storm compared to before.…”
Section: Defining the Ecology And Changing Epidemiology Of Coccidimentioning
confidence: 99%